2013
DOI: 10.1155/2013/390967
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriInfection and Anemia in Taiwanese Adults

Abstract: Background. Chronic Helicobacter pylori infection and iron-deficiency anemia (IDA) are common in adults. Although the most common causes of IDA usually arise from the gastrointestinal tract, the association between chronic Helicobacter pylori infection and anemia remains unclear. Aim. To evaluate the association of chronic Helicobacter pylori infection and IDA. Materials and Methods. We enrolled 882 patients from January 2010 to April 2013. The status of Helicobacter pylori (H.p) infection was confirmed and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…A stronger positive association between H. pylori infection and ID was found in a subgroup analysis of studies that adjusted for confounders (OR 1.41, 95% CI 1.17–1.71), Pv<.001. Separate meta‐analyses of pediatric and adult studies that adjusted for confounders showed similar results (OR 1.43, 95% CI 1.15–1.78) and (OR 1.37, 95% CI 1.01–1.86), respectively, while such association was nonsignificant (OR 1.21, 95% CI 0.94–1.56; Pv=.13) in a meta‐analysis of unadjusted results …”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…A stronger positive association between H. pylori infection and ID was found in a subgroup analysis of studies that adjusted for confounders (OR 1.41, 95% CI 1.17–1.71), Pv<.001. Separate meta‐analyses of pediatric and adult studies that adjusted for confounders showed similar results (OR 1.43, 95% CI 1.15–1.78) and (OR 1.37, 95% CI 1.01–1.86), respectively, while such association was nonsignificant (OR 1.21, 95% CI 0.94–1.56; Pv=.13) in a meta‐analysis of unadjusted results …”
Section: Resultsmentioning
confidence: 80%
“…The 44 studies that scored 12 points or less in the quality assessment score were therefore excluded from the meta‐analysis. Fifty observational studies addressed the outcomes IDA, ID, and/or anemia and met inclusion criteria (Table ) . These studies varied in their design, study population, and method of detecting H. pylori infection; in their classification of IDA, ID, and/or anemia; and in their findings (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… did not find any significant association between H. pylori infection and serum levels of prohepcidin, while this biomarker was decreased in patients with atrophic gastritis. Finally, the results of three recent studies did not support any association between H. pylori infection and IDA ; however, the occurrence of some biases, such as the exact definition of IDA or the absence of information concerning the specific gastric histologic patterns shown by patients, may, in our opinion, affect the results of studies performed on this important issue.…”
Section: Hematological Diseasesmentioning
confidence: 68%